Getting the measure of your business (Cambridge University Press, 2002)
The main purpose of this book is to provide directors, managers, change agents and consultants with simple but effective tools to help design and implement performance measurement systems, such as the Balanced Scorecard. It contains specific tools which will be of interest to practicing managers and consultants. These tools and techniques have been developed over many years and honed through application in companies such as Rolls-Royce Aerospace and Federal Mogul. Besides large multi-nationals, the techniques have also been used effectively in medium and smaller sized entreprises and are appropriate to any manufacturing company employing 50 people or more.